قياس رضا زبائن البنوك التجارية الجزائرية لجودة الخدمة المصرفية المقدمة دراسة ميدانية - أولاد حيمودة, عبد اللطيف; شنيني, عبدالرحيم; علماوي, أحمد (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة إلى معرفة أثر جودة الخدمات المقدمة من طرف البنوك التجارية الجزائرية على رضا عملائها، حيث قمنا بدراسة ميدانية في كل من "البنك الوطني الجزائري، القرض الشعبي الجزائري، بنك البركة الجزائري"، و تم توزيع استبيان على عملاء تلك البنوك في ولاية غارداية، حيث بلغ عددهم 313 عميل، تمثلت أهم النتائج في أن لبعد التعاطف أهمية كبيرة في تحقيق رضا العملاء مقارنة بالأبعاد الأخرى، ثم يليه بعد الاعتمادية، ثم الملموسية ، ثم الأمان، وفي الأخير نجد بعد الاستجابة، ما يعني أن طبيعة الاستجابة الفورية لاحتياجات العملاء ومعالجة شكاويهم على مستوى البنوك محل الدراسة ليست في المستوى من وجهة نظر العملاء، وهذا ما يؤثر سلبا على مستوى جودة الخدمات المصرفية المقدمة. The study aimed to know the impact of the services quality provided by Algerian commercial banks on their customers’ satisfaction. Field study method was conducted in each of the "National Bank of Algeria, the Algerian Popular Loan, and the Algerian Baraka Bank", A questionnaire was distributed on sample of banks’ clients (313) in the state of Ghardaia. The most essential results were the dimension of empathy that has great importance in achieving customer satisfaction compared to other dimensions, then it is followed by reliability, tangibility, security, and the last dimension is the response, which means that the nature of the immediate response to the needs of customers and the handling of their complaints at the level of the banks under study as not as the customers' perceived, and this negatively affects the quality of the banking services provided.
Measuring the satisfaction of customers of Algerian commercial banks with the quality of banking service provided, -A field study "CPA, BNA, BBA
مقال
Keywords: جودة الخدمة المصرفية ; رضا الزبائن ; عميل مصرفي; Quality of Banking Service ; Customer satisfaction ; Bank Client